Regulatory frameworks for reforms of state-owned enterprises in Thailand and Malaysia - Pornchai Wisuttisak; Nasarudin Abdul Rahman (Asian Development Bank Institute (ADBI), 2020)
This paper studies the experience of regulatory reform of state-owned enterprises (SOEs) in Thailand and Malaysia. It explores the trends of regulatory reforms relating to the creation of privatization, liberalization, and competition. The paper focuses on the development of the regulatory reforms of SOEs in major sectors (airlines, energy, and telecommunication) in Thailand and Malaysia. It argues that, while having active plans for regulatory reforms, the implementation of these reforms may not successfully fulfill the aims in terms of the efficiency of SOEs. The regulatory reforms face challenges regarding the political economy, regulatory barriers for sectoral restructure, and regulatory intervention approaches in both countries. The paper concludes by proposing possible developments of the regulatory frameworks for the reform of SOEs.
Keywords: K23; 330; privatization; regulation; Thailand; Malaysia